Figuring the pecking order: Emerging child food preferences when species meet in the family environment. (12th November 2018) - Bettany, Shona M.; Kerrane, Ben
Abstract : Purpose: Using the family activity of hobby stock-keeping ("petstock") as a context, this paper aims to extend singularization theory to model the negotiations, agencies and resistances of children, parents and petstock, as they work through how animals become food within the boundaries of the family home. In doing so, the authors present an articulation of this process, deciphering the cultural biographies of petstock and leading to an understanding of the emergent array of child animal food-product preferences. Design/methodology/approach: Data were collected from petstock-keeping parents through a mixture of ethnographic, in-depth interviewing and netnographic engagements in this qualitative, interpretive study; with parents offering experiential insights into animal meat and food-product socialization behaviours played out within the family environments. Findings: The findings discuss the range of parental behaviours, motivations and activities vis-à-vis petstock, and their children's responses, ranging from transgression to full compliance, in terms of eating home-raised animal food-products. The discussion illustrates that in the context of petstock, a precocious child food preference agency towards animal meat and food products is reported to emerge. Research limitations/implications: This research has empirical and theoretical implications for the understanding of the development of child food preference agency vis-à-vis animal food products in the context of family petstock keeping. Practical implications: The research has the potential to inform policy makers around child education and food in regard to how child food preferences emerge and can inform marketers developing food-based communications aimed at children and parents. Originality/value: Two original contributions are presented: an analysis of the under-researched area of how children's food preferences towards eating animal food products develop, taking a positive child food-choice agency perspective, and a novel extension of singularization theory, theorizing the radical transformation, from animal to food, encountered by children in the petstock context.